Chaveador wireless para teclado e mouse - Bragagnolo, Dennis Guilherme de Macedo (2022)
Working from home has been a trend in recent years and has gained a monumental scale due to the coronavirus pandemic that started in 2020, when about 11 percent of Brazilians workers worked in this modality. Along with remote work, the concerns about ergonomics and workers’ mental health also gained strength, especially considering that the residential environment does not always have the appropriate structure for the remote work and often not even area available for a redesign, which requires the best possible use of space. In order to provide this better use of space for those workers who use more than one computer, usually one personal and other from the company, the project proposes to use the same set of keyboards and mouse through a switching device that does not demand the physical exchange of connectors. Apart of reducing the number of peripherals on users’ tables and benches, the proposed switch also has the potential to reduce the number of cables by using one of the wireless technologies available on the market, the Bluetooth Low Energy. Aiming to provide the utilization of the user’s preferred keyboards and mice, without tying them to a few layouts, the proposed switch is not bound to a specific peripheral, but has an USB port for connecting devices. In this way, with the use of the wireless switch, the user gains in harmony in their residential-work environment, contributing to their wellbeing and productivity at a very reasonable production cost of just over a hundred Brazilian reais.